(untitled) (Journal of The Colloquium for Information Systems Security Education, 2022)
Due to the recent pandemic, video conferencing platforms – once niche products aimed at limited communities have become a pervasive way of conducting business and sustaining social connections on a global scale. This project explored cybersecurity vulnerabilities and risks faced by these platforms – their data, hardware, and the information exchanged during virtual meetings – and explains some ways these issues can be mitigated. Published research was compiled and analyzed to uncover general risks, vulnerabilities, and security measures. Then, three popular platforms – Zoom, Skype and GoToMeeting were subjected to closer scrutiny. Findings show that platform vendors, business organizations, education institutions, and end users all bear responsibility to train themselves and their constituents on specific cybersecurity steps to enhance video conferencing security. Targeted recommendations are shared, along with some opportunities to build upon this research in the future.